Education for sustainable construction - Bragança, L. (2011)
The COST Action C25 "Sustainability of Constructions - Integrated Approach to Life-time Structural Engineering" is a network of scientists and researchers from 28 European countries and the EU Joint Research Centre in Ispra. It was established to promote science-based developments in sustainable construction in Europe through research on life-time structural engineering. The COST Action has been active since 2006.